2021
DOI: 10.2478/aoas-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of OPN and AREG Genes in Relation to Transcript Expression of a Panel of 12 Genes Controlling Reproduction Processes and Litter Size in Pigs

Abstract: The aim of this study was to define the transcript expression of 12 genes, identify new polymorphisms in selected 2 genes and to estimate the association between the level of expression, gene polymorphism and litter size in sows. Two groups of sows were selected: 71 crossbred sows and 328 purebred sows. For transcript analysis endometrial tissue samples were collected, while blood was sampled for the purpose of DNA polymorphism analysis. For all animals data on litter size and weaned piglets were obtained. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Recently, there seems to be a significant relationship between purebred sows carrying the OPNe6-462 and OPNp3-617 genotypes and piglet size and the number of weaned piglets. 17 Numerous in silico analyses confirmed the damaging effects of the p.Q>R234 SNP on the structure, biological functions, and stability of OPN; for example, a deleterious nsSNP may adversely affect OPN’s ability to perform its function. Consequently, the greater frequency of p.Q>R234 results in damaged OPN synthesis leading to lower prolificacy of Awassi ewes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, there seems to be a significant relationship between purebred sows carrying the OPNe6-462 and OPNp3-617 genotypes and piglet size and the number of weaned piglets. 17 Numerous in silico analyses confirmed the damaging effects of the p.Q>R234 SNP on the structure, biological functions, and stability of OPN; for example, a deleterious nsSNP may adversely affect OPN’s ability to perform its function. Consequently, the greater frequency of p.Q>R234 results in damaged OPN synthesis leading to lower prolificacy of Awassi ewes.…”
Section: Discussionmentioning
confidence: 96%
“… 14 Moreover, many variations have been identified in the OPN ( SPP1 ) gene with production traits in cattle, 15 and reproductive traits and litter size in pigs. 13 , 16 , 17 Based on the above literature review, very few studies have been conducted on genetic polymorphisms in the OPN gene in relation to their association with cattle prolificacy, and to the best of our knowledge, no studies have been conducted regarding their association with sheep prolificacy.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies by Terman [ 46 ] indicated that PRLR significantly affects the litter size of pigs; however, its association signals of variants to these genes with litter size are inconsistent among different lines or groups. Some studies have also reported that non-synonymous SNPs of the OPN gene had an association with litter size traits in pigs [ 47 , 48 , 49 ]. With respect to the reproductive traits in the Large White pig breed, data from the present study showed no significant difference while determining the statistical analysis based on the RIP-VMP1-12, RIP-PRLR-6, and RIP-OPN-1 polymorphic types.…”
Section: Discussionmentioning
confidence: 99%